Kewenangan Komisi Pengawas Persaingan Usaha Republik Indonesia dalam Sistem Peradilan di Indonesia - Derin Fernanda Ainun Nisa; Rumawi Rumawi; Ahmad Junaidi; Supianto Supianto; Mohammad Ali; Udiyo Basuki; Sri Astutik; Asmarani Tri Andari (JURNAL RECHTENS, 2026)
The KPPU has the authority to act as an investigator and decision-maker in cases that have the potential to be misused on a large scale. The KPPU's decision-making authority complicates its position in the state system, especially considering its multifunctional role. The objectives of this study are: 1. To explain the KPPU's authority. 2. To describe the KPPU's authority in the judicial system. This study uses a statutory approach and a conceptual approach. The results of the study indicate that 1. Based on the explanation above, the essence of the KPPU's authority, as outlined by Indonesian competition law, is as follows: First, Investigation, Second, Examination, Third, Evidence, Fourth, Sanctions and Decisions, Fifth, Supervision and Law Enforcement. 2. Determining the limits of a state's power has become an important component in running a state system. As explained by Jimly in his research, which mentions the true concept of the separation of powers of a state. Then, regarding the duties and authorities held by the KPPU, the researcher assesses that this does not deviate from the principle of limiting state power. Because the implementation of these authorities and duties falls within the domain of the executive branch of government and administrative functions, the KPPU has extensive authority to decide cases and impose sanctions, which are not far from administrative sanctions